Letter - Schiff, Victor
1936-08-16 Daily Herald JACK SANDFORD PARIS CORRESPONDENT 61 RUE LA FAYETTE PARIS 9e TELEPHONES TRUDAINE 02 63 TO 02 69 TELEGRAMS DLYHERALD, PARIS Sir Walter Citrine Transport House Smith Square London My dear Citrine, I have been urgently asked by Senor comarera, Catalonian Socialist MP in the Spanish Cortes and leader of the U.G.T., the General Workers' Union affiliated to the IFTU to send you as quickly as possible a report describing the situation from the UGT point of view. Since, as I understand, Mr. Helsby will communicate with you about my article, which they hesitate to publish before consulting with you, I can make this report quite short, as the main points are already developed in more or less veiled form in that article. Yours sincerely, Victor Schiff 292/946/10/144